(untitled) (Central Asian Journal of Medical Sciences, 2024)
Objectives: Hepatocellular carcinoma (HCC) emerged as a global health concern in 2020, ranking as the sixth most diagnosed cancer and the third leading cause of cancer-related death. This study analyzed predictors of 6-month relapse in early-stage HCC patients after Radiofrequency Ablation (RFA). Methods: This retrospective study, from January 1, 2018, to December 31, 2022, meticulously explored ablation methods for early-stage HCC treatment. Data collection included a 6-month relapse definition, demographic details, and tumor-related variables. Results: Over five years, 483 participants underwent RFA for early-stage HCC, presenting diverse demographic and tumor-related profiles. Significant associations were found between relapse and factors such as gender, smoking, alcohol use, tumor size, specific tumor locations, and pre-treatment AST levels. Notably, 6.8% of participants experienced relapse within six months. In the multivariate analysis, adjusting for confounders, smoking (p = 0.014), tumor size > 3cm (p < 0.001), tumor location S2 (p < 0.001), and pre-treatment AST levels (p = 0.015) remained significant predictors. Conclusion: This study sheds light on the complex dynamics of 6-month relapse in early-stage HCC patients, emphasizing the significance of predictors such as smoking, tumor size, tumor location, and pre-treatment AST levels.